Strategic Planning for Control of Ownership of Population Documents in Denpasar City - Sulasteri, Nyoman Rai Sri (Journal of A Sustainable Global South, 2025)
Population administration is a series of structuring and controlling activities toward documents and population data so that every citizen has rights and responsibility for fulfilling population administration regulations. The ownership of population administration is very important for various purposes. In order to create the services as expected by the community, the Civil Registry Service Office of Denpasar City is trying to overcome any obstacles and limitations, such as human resource and budget limitations that refer to principles of public services that are transparent, fair, effective and accountable in accordance with applicable rules. As for the realization of the performance of the Civil Registry Service Office of Denpasar City when compared with medium goals and objectives, and if it is compared with national standards then the performance achievement of Family Card (a household membership document) ownership, issuance of Death Certificates, ownership of Birth Certificates, and issuance of Marriage Certificates have been achieved. Meanwhile, the performance achievement of Electronic Identity Card ownership not yet achieved. Index Terms — population administration-rights and obligations-very good achievement .